Pengalaman Perempuan dalam Menghadapi Beauty Privilege dan Diskriminasi di Tempat Kerja - Bunga Sabrina Eka Abelia; Ulilababil Ulilababil; Rauly Sijabat (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study explores women’s experiences of discrimination in the workplace due to beauty privilege. This study uses a qualitative approach with in-depth interview techniques, participant observation, and questionnaires to uncover forms of discrimination. This phenomenon creates injustice and has negative impacts on individuals who do not meet beauty standards, such as feelings of inferiority, alienation, and limited career opportunities. This study recommends the importance of awareness and more inclusive policies to reduce appearance-based discrimination in the workplace. The findings show that beauty privilege often provides advantages for individuals who are considered physically attractive, but also creates psychological stress for those who do not meet certain beauty standards.